Comparative Analysis Of Mechanical Properties Of Rubber-Kenaf-Wire-Cotton Lamination On Epoxy-Carbon-Ramie Composite - I Komang Astana Widi (Widyagama University of Malang, 2020)
The use of fiber has been widely researched but the use of several fibers as reinforcement does not necessarily result in optimal mechanical properties. This study aimed to determine the tensile strength and impact strength of composite materials using an epoxy matrix with the addition of rubber variations to increase the ductility of the matrix. Meanwhile, the fibers used for reinforcement are carbon fiber and ramie. In this study, the reinforcement added a variety of kenaf fiber, wire and cotton. This was to compare the role of kenaf fiber, wire and cotton in improving the mechanical properties of composite materials. The percentage of rubber volume fraction added to the epoxy is 30%, 40% and 50%.The highest tensile test results were shown in the 30% epoxy rubber-carbon fiber-ramie fiber-kenaf specimen which was 10.67 Kgf / mm2, and the lowest result was the epoxy 50% rubber-carbon fiber-ramie-wire specimen, which was 5.752 kgf / mm2. The fracture analysis of the tensile test showed that the fracture area is formed by debonding phenomena between fibers and matrices.The highest impact strength was found in the 50% epoxy rubber-carbon fiber-ramie-wire specimen, which was 0.039 kgf / mm2. Meanwhile, the lowest impact strength was found in the 40% epoxy rubber-carbon fiber-ramie fiber-cotton specimen, which was 0.030 kgf/ mm2. In general, the trend of impact test data shows that as the percentage volume fraction of rubber increases, the impact strength of the composite material increases.Based on the test analysis, it was concluded that increasing the percentage of rubber will increase the impact strength of the woven wire reinforcement. However, the impact strength is inversely proportional to kenaf fiber reinforcement, where the addition of the percentage of rubber will reduce the impact strength. This showed that the mechanical properties were not always influenced by the percentage of rubber but were very dependent on the type of fiber. This was also shown in the results of the tensile strength test. In general, it was known that the adhesion between fiber and matrix laminates affected the mechanical properties in addition to the strength of the reinforcement.